PENGARUH RELIGIUSITAS DAN PROFIT MARGIN TERHADAP TINGKAT PERKEMBANGAN JUMLAH NASABAH DI BANK SYARIAH MANDIRI GARUT - Yasir Muharram Fauzi (Jurnal Maps (Manajemen Perbankan Syariah), 2017)
Various previous studies show different results. Religiosity/emotional variables, for example, turn out to be the main factor of public preference for choosing Islamic banks for the people of Central Java. While for the people of West Java and East Java was religiosity / religiosity does not become the main factor of choice and preference for the utilization of sharia banks. On the other hand shows that the growth of DPK in 2004 of sharia banks in Central Java reached 247.81% exceeds the national level of only 106.55%. On average, the growth of Islamic banking DPK in Central Java between 2004 and 2009 was 74.87%. While the national level between 2004 to 2009 only ranged 45.14%. Consumer preferences according to the concept of sharia are not based on the spirit of the value of rationalism and utilitarianism, but based on the value of "falah" Chapra, (2001) which in Weber's theory (1969) is called the value of religious absolutism. Utilitarianism refers only to satisfaction based on rationality of benefit (F) calculation of economical, while falah refers to the consideration of the benefit (M). The above conditions will affect the behavior of one's economic choices against conventional banking savings products that only contain elements of F, or Islamic banking that contains elements of M. This research uses a survey method used for explanatory research method that is explanatory research Causal relationships between variables through hypothesis testing. The results showed that the variable religiosity and profit margin variables showed a significant effect on the level of development of the number of customers. The prediction ability of the two variables to the level of the development of the number of customers in this study amounted to 19.3%, while the rest influenced other factors not included in the study.